Beating lady luck : effects of competitive gambling on opponent likeability and targeted physical aggression - Wee, Kenneth Zong Hao (2015)
Gambling is a pastime enjoyed by many people. However, while there are many correlational studies documenting the potential negative consequences, experimental studies are far and few between. The aim of this study was to investigate the causal effects of competitive gambling on opponent likeability and targeted physical aggression. Specifically, this study hypothesised that 1) losers would perceive their opponents to be less likeable; and 2) losers would be physically more aggressive towards their opponents. In addition, social gambling motives were proposed to moderate the lose-aggression relationship, while likeability and frustration were proposed to mediate the lose-aggression relationship. An indirect effect of gambling outcomes and likeability on aggression through social motives was also proposed. Ninety-eight university undergraduates, who were largely recreational gamblers, participated for either course credit or a cash voucher. The Balloon Analogue Risk Task (BART) was adapted as a simulation of a competitive gambling game while the Hot Sauce Paradigm was adapted as a measure of targeted physical aggression. Results indicated that losers indeed perceived their opponents to be less likeable. More importantly, losers were more aggressive, and this relationship was moderated by social motives and mediated by likeability but not frustration. The indirect effect of gambling outcomes and likeability on aggression through social motives was also supported. Potential limitations and implications of this study were discussed.